Effect of age on the cardiovascular remodelling induced by chronic intermittent hypoxia as a murine model of sleep apnoea. Issue 3 (18th June 2019) - Castro‐Grattoni, Anabel L.; Suarez‐Giron, Monique; Benitez, Ivan; Torres, Marta; Almendros, Isaac; Farre, Ramon; Montserrat, Josep M.; Dalmases, Mireia; Gozal, David; Sánchez‐de‐la‐Torre, Manuel; ,
ABSTRACT: Background and objective: Chronic intermittent hypoxia (CIH) is a major determinant of the cardiovascular morbidity associated with obstructive sleep apnoea (OSA), and the magnitude of CIH impact may be influenced by ageing. Here, we assessed the role of ageing in the early cardiovascular structural remodelling induced by severe CIH in a murine model of OSA. Methods: Cardiovascular remodelling was assessed in young (2 months old, n = 20) and aged (18 months old, n = 20) C57BL/6 female mice exposed to CIH (20% O2 for 40 s, 5% O2 for 20 s) or normoxia (room air) for 8 weeks (6 h/day). Results: Early vascular remodelling was observed in young mice exposed to CIH as illustrated by intima‐media thickening (mean change: 4.6 ± 2.6 μm; P = 0.02), elastin fibre disorganization (mean change: 9.2 ± 4.5%; P = 0.02) and fragmentation (mean change: 2.5 ± 0.8%; P = 0.03), and collagen (mean change: 3.2 ± 0.6%; P = 0.001) and mucopolysaccharide accumulation (mean change: 2.4 ± 0.8%; P = 0.01). In contrast, vascular remodelling was not apparent in aged mice exposed to CIH. Furthermore, left ventricular perivascular fibrosis (mean change: 0.71 ± 0.1; P  < 0.001) and hypertrophy (mean change: 0.17 ± 0.1; P = 0.038) were increased by CIH exposure in young mice, but not in aged mice. Principal component analysis identified similar cardiovascular alterations among the young mice exposed to CIH and both older mouse groups, suggesting that CIH induces premature cardiovascular senescence. Conclusion: Cardiovascular remodelling induced by severe CIH is affected by the age at which CIH onset occurs, suggesting that the deleterious cardiovascular effects associated with CIH may be more pronounced in younger populations, and such changes resemble chronological age‐related declines in cardiovascular structural integrity. Abstract : Chronic intermittent hypoxia (CIH) is a major determinant of cardiovascular morbidity associated with obstructive sleep apnoea (OSA), but its adverse impact may be influenced by ageing. We show that deleterious cardiovascular effects associated with CIH are not evident in aged mice, and early cardiovascular ageing may be potentiated by CIH in young mice. See related Editorial